2017
DOI: 10.1247/csf.17015
|View full text |Cite
|
Sign up to set email alerts
|

Deltamethrin Increases Neurite Outgrowth in Cortical Neurons through Endogenous BDNF/TrkB Pathways

Abstract: ABSTRACT. Deltamethrin (DM), a type II pyrethroid, robustly increases brain-derived neurotrophic factor (Bdnf) expression and has a neurotrophic effect in primary cultures of rat cortical neurons. In this study, we investigated the effect of DM on neurite morphology in cultured rat cortical neurons. DM significantly increased neurite outgrowth, but this increase was abolished when the BDNF scavenger tropomyosin receptor kinase B (TrkB)-Fc was added 10 min before the DM treatment. In contrast, the addition of T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…2007). It was reported that DM at 1μM increased neurite outgrowth in rat cortical neurons through endogenous BDNF/tropomyosin receptor kinase B pathways (Ihara et al. 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2007). It was reported that DM at 1μM increased neurite outgrowth in rat cortical neurons through endogenous BDNF/tropomyosin receptor kinase B pathways (Ihara et al. 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Another factor that may also contribute to the discrepancy could be the exposure duration. We treated neurons for 48 h and 6 d commencing 3 h after plating for axon growth and dendritic complexity measurements, respectively, while in the previous study, neurons were exposed at 7 DIV for 3, 6, 12, and 24 h, respectively (Ihara et al. 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Further, it is also proved that mutations that disrupt the binding of CREB can, in turn, reduce BDNF responses demonstrating the interplay between these two signaling molecules [ 21 ]. Deltamethrin, an insecticide that belongs to the pyrethroid family, increases neurite outgrowth in cortical neurons by activating the endogenous BDNF/TrkB pathway[ 39 ]. Cypermethrin, chlorpyrifos, deltamethrin, and imidacloprid exposure upregulates the mRNA and protein levels of BDNF in the brain of adult zebrafish [ 40 ].…”
Section: Pesticides and Neurotoxicitymentioning
confidence: 99%
“…For dendritic morphology analysis, images captured with a BX50-34LFA-1 (Olympus) fluorescent microscope were used for Sholl analysis. The previously described Sholl analysis procedure (Ihara et al, 2017;Ishikawa et al, 2010Ishikawa et al, , 2014 was performed with minor modifications. All analysis was applied to neurites of MAP2 and GFP double-positive neurons without a thin and long neurite in a blind manner.…”
Section: Analysis Of Dendritic Morphology and Cellular Localization Of Mrtfbmentioning
confidence: 99%